The Pope as Antichrist: the Substance of George Tyrrell's Polemic - Wells, David F. (Harvard theological review, 1972)
George Tyrrell's identification of the Pope as the Antichrist was not particularly original but it was important. For Tyrrell was the leader of a movement which, in the opinion of René Marlé, created the most serious disturbance in the Catholic Church since the time of the Reformation. Moreover, the reformers and iconoclasts who had made this charge previously had usually done so from a position outside of Catholic tradition. Tyrrell, however, attacked the Pope from within, as a member of his flock. The Jesuit philosopher even went so far as to claim that his radical posture was the inevitable consequence of his Catholic convictions. Thus he explained:I believe in the Roman Church so far as it is Christian and Catholic; I disbelieve in it so far as it is papal. I see two spirits in it, as in myself, struggling for supremacy Light and Darkness, Christ and Anti-Christ; God and the Devil. At present Christ is thrown and Anti-Christ is uppermost. I look for the day when Peter, after his boasted fidelity and manifold denials, aliquando conversus, confirmabit fratres. It is a long way off from that blessed cockcrow.